Mechanotransduction channel Piezo is widely expressed in the spider, Cupiennius salei, mechanosensory neurons and central nervous system - Jessica A. G. Johnson (Nature Portfolio, 2021)
Abstract Mechanosensory neurons use mechanotransduction (MET) ion channels to detect mechanical forces and displacements. Proteins that function as MET channels have appeared multiple times during evolution and occur in at least four different families: the DEG/ENaC and TRP channels, as well as the TMC and Piezo proteins. We found twelve putative members of MET channel families in two spider transcriptomes, but detected only one, the Piezo protein, by in situ hybridization in their mechanosensory neurons. In contrast, probes for orthologs of TRP, ENaC or TMC genes that code MET channels in other species did not produce any signals in these cells. An antibody against C. salei Piezo detected the protein in all parts of their mechanosensory cells and in many neurons of the CNS. Unspecific blockers of MET channels, Ruthenium Red and GsMTx4, had no effect on the mechanically activated currents of the mechanosensory VS-3 neurons, but the latter toxin reduced action potential firing when these cells were stimulated electrically. The Piezo protein is expressed throughout the spider nervous system including the mechanosensory neurons. It is possible that it contributes to mechanosensory transduction in spider mechanosensilla, but it must have other functions in peripheral and central neurons.